PERANCANGAN SISTEM KENDALI SMART HOME MENGGUNAKAN NODMCU ESP8266 BERBASIS IOT TERINTREGASI SENSOR CAHAYA DENGAN METODE R&D - Ali Imron, Muhammad; Mashuri, Chamdan; Kistofer, Terdy; Kristianto, Hery (Inovate, 2023)
The control system is an integrated part of today's modern life system. For example: room temperature control,washing machines, robots, airplanes, and so on. In the era of analog technology development, electrical devices aregenerally controlled manually by the user. Someone has to turn on and off the switch directly connected to the electricaldevice. Sometimes, there are some electrical devices that are found still alive when not in use, this can be caused by theuser's negligence to turn off these electrical devices. If there are quite a number of electrical devices in a house, it willbe very ineffective and inconvenient to manually turn off and on these electrical devices. To overcome this problem, acontrol system or smart home is proposed where the system is expected to be time efficient and minimize electricitywastage. The research method that will be used is the R&D method, namely developing products and validating theseproducts so that they become new products that meet needs. The new product is developed through systematicprocedures and field trials so that it meets certain quality criteria or standards, effectiveness and efficiency. In thisresearch using NodeMCU and ralay to store data and manage several commands that have been stored into NodeMCUthen commands are given to relays whose job is to connect and disconnect electric currents, for control devices coupledwith light sensors. To control the tool using Google Home, from the test results it was found that the NodeMCU, therelay and the light sensor were running according to the command.Key Words : Smart Home, Internet Of Things (IoT), Light Sensor